Application Of Liquid Organic Fertilizer From Moringa Leaves (Moringa Oleifera) On Sweet Plants (Brassica Juncea L) - Praditya, Ade; Elizabeth Mustamu, Novilda; Ainy Dalimunthe, Badrul; Lestari, Widya (International Journal Of Community Service, 2024)
Liquid Organic Fertilizers Are Fertilizers Made From Plants That Have Been Heated, And The Product Is Liquid. The Purpose Of This Community Service Activity Is To Increase Public Knowledge About Liquid Organic Fertilizers And Skills In Making Poc. This Service Method Consists Of Preparation, Implementation, Monitoring, And Evaluation. Communities Can Make Their Own Poc And Apply It To Plants. And The Processing Results Can Be Used By The Community. The Research Method Used Was 3 Treatments And 4 Replications With A Completely Randomized Design (Crd). This Study Aims To Determine The Effectiveness Of The Combination Of Liquid Organic Fertilizer Of Moringa Leaves On The Growth Of Mustard Greens (Brassica Juncea L).